“Evaluación de la atención al cliente a través del Modelo Servqual en el Paradero Sabor Latino del cantón Pallatanga del período 2018” - Josselyn Jimena, Sanabria Álava (2020)
In the present research work, the State of the Art encompasses the background of previous research related to the proposed theme that will serve as references on the Servqual Model, the Theoretical Foundation, the relationship between the quality of the service and the Servqual model is reviewed. In Unit I, the generalities of the Paradero Sabor Latino are analyzed, such as its mission, vision, and structural organization chart. Unit II, it is about quality, its definitions and evolution, the Deming cycle, the service. quality of the service, indicators to measure the quality of the service, the customer, the Servqual Model, and its dimensions. In Unit III, the current situation of the location is analyzed. The Servqual questionnaire model is made; the Cronbach Alpha is performed to determine the reliability of the questionnaire to be used. The methodology includes the type of research, the design of the research, the population and sample, the research method, data collection techniques and instruments, processing techniques for the analysis of results. In the Analysis and Discussion of results, there are results, there are the results achieved during the conduct of the survey, where the strategies that will be used to reduce the existing gaps are considered. Finally, the conclusions and recommendations are presented, finding that the clients define their expectations and their perception, following the service provided by the whereabouts, where they create gaps and through this research create proposals for strategies to eliminate these gaps.